Forms and Historical and Cultural Roles of Traditional Governance (Ondoafi/ondofolo) in the Governance of Indigenous Communities in Jayapura Regency, Papua Province - Kendi, Ibrahim Kristofol; Ibrahim, Muh. Akmal (KnE Social Sciences, 2025)
This study aims to analyze the forms and historical and cultural roles of the traditional governance of Ondoafi/Ondofolo in the governance of indigenous communities in Jayapura Regency, Papua. The traditional governance in this area holds a significant position within the social structure of the community and plays a strategic role in preserving cultural values, mediating conflicts, and regulating land and natural resource rights. The existence of Ondoafi/Ondofolo is culturally and spiritually legitimate. However, it has not been fully integrated functionally into the village governance system established by the state, especially after the implementation of Papua’s special autonomy. This study employs a qualitative approach with a case study method in several villages in Jayapura Regency. Data were collected using document studies. The research findings indicate that the traditional governance of Ondoafi/Ondofolo is characterized by genealogical and collective leadership, with roles encompassing spiritual, social, and ecological aspects. However, there is an imbalance in the relationship between traditional governance and formal governance, often leading to overlapping authority and disharmony in village development implementation. The study reveals that co-optation occurs when the government takes over customary roles without involving traditional leaders, rendering traditions merely symbolic. Hybridization occurs when customary and modern systems integrate, such as in customary deliberations involving village apparatus. Marginalization arises when customary roles are sidelined by formal policies. Institutional transformation is dynamic, encompassing co-optation, hybridization, and marginalization, reflecting the contextual interaction between customary and formal governance within village administration. Strengthening the role of Ondoafi in Jayapura Regency is carried out through accommodative policies based on local wisdom, such as the regional regulation on the recognition of traditional governance. Role optimization is achieved through the village customary council (DAK), village development planning discussions (Musrenbang) based on customary dialogue, and governance training for traditional leaders to enhance capacity and effective participation.